2015
DOI: 10.21273/hortsci.50.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Appropriate Leaf Sampling Period for Nutrient Analysis in ‘Hass’ Avocado

Abstract: This research was carried out from 2004 to 2005 in two commercial ‘Hass’ avocado orchards cultivated under rainfed conditions in a hot subhumid climate of the state of Nayarit, Mexico. The objectives of this study were to: 1) establish the patterns in nutrient concentrations during the lifespan of winter and summer vegetative flush leaves; and 2) validate a methodology based on mathematical functions to identify the appropriate period for leaf sampling to diagnose plant nutrition in avocado considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…High N and low Ca levels in the exocarp of avocado could be associated with anthracnose and lower postharvest quality. Salazar-García et al (2015) mentioned that variations in Ca concentrations in leaves of vegetative shoots are very similar, and these also increase with age. Lahav et al (1990) found that Ca in leaves of the previous years was higher than those of summer leaves.…”
Section: Calcium Nutritional Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…High N and low Ca levels in the exocarp of avocado could be associated with anthracnose and lower postharvest quality. Salazar-García et al (2015) mentioned that variations in Ca concentrations in leaves of vegetative shoots are very similar, and these also increase with age. Lahav et al (1990) found that Ca in leaves of the previous years was higher than those of summer leaves.…”
Section: Calcium Nutritional Dynamicsmentioning
confidence: 99%
“…In our case, the concentration of 2.7 % was obtained. Silber et al (2018) mentioned thattotal N in 'Hass' fruits increase from the beginning of inflorescence until fruit set, and then decrease during fruit development (Salazar-García et al, 2015). After fruit set, in new fruit development, Lovatt (1995) and Salvo (2017) declared that the highest N demands occur due to the competition between fruit and new shoot formation; however, if there are reserves in the soil and small branches, fertilization is not required (Lahav et al, 1990;Rosecrance et al, 2003).…”
Section: Nutritional Dynamics Of Total Nitrogenmentioning
confidence: 99%
“…Therefore, it would not be recommended to sample leaves for foliar diagnosis purposes in periods within or close to this phenological phase. According to Salazar-García et al (2015), the most suitable period for collecting leaves for foliar diagnosis is the one where the levels of the nutrients of interest are more stable.…”
Section: Seasonal Nutrient Content Variation In Avocado Leavesmentioning
confidence: 99%
“…However, there are indications that the leaf nutrient content of fruit plants varies depending on the time of year and phenology (LEONEL et al, 2012;CRUZ et al, 2019), which must occur at different times for different genotypes and different edaphoclimatic conditions. Studies carried out to identify the best time for leaf sampling in various avocado cultivars suggest that leaf collection should be carried out in the period of greater nutrient content stability (SALAZAR-GARCÍA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf-N status is frequently used for fertilization-management decisions in the mango industry (Hundal et al, 2005; Raghupathi et al, 2005; Raj and Rao, 2006; Pinto et al, 2007; Kumar et al, 2015; Salazar-Garcia et al, 2018). However, leaves may remain attached for several years on mango trees (Pinto et al, 2007), and the N-fertilization thresholds may vary with factors such as seasonal aspects (Urban et al, 2006), leaf age, rootstock, physiological and phenological status, distance from the inflorescences or fruit (Urban et al, 2004b; Pinto et al, 2007) and fruit:leaf ratio (Urban and Léchaudel, 2005).…”
Section: Introductionmentioning
confidence: 99%